ANALISIS PEMAHAMAN KONSEP IPA SISWA KELAS IV SD NEGERI 232 TADANG PALIE PADA MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI - Sudarto , Sudarto; Asriadi, Asriadi; Muhammad Arham (Jurnal Cakrawala Ilmiah, 2025)
This research is a descriptive qualitative research, which aims to analyze the ability to understand the concept of science of grade IV students of SD Negeri 232 Tadang Palie, Sibulue District, Bone Regency on plant material that is the source of life on earth and the factors that influence it. The subjects in this study are grade IV teachers and grade IV students. Teachers consist of 1 respondent and 6 students as many as respondents. The data collection techniques in this study were obtained from the results of interviews and class observations. The data analysis technique in this study starts from the stage of data reduction, data presentation, and conclusion drawn. The results of this study show that students' understanding of science concepts varies according to their level of understanding, students with high understanding are able to restate concepts well, classify plant parts according to their functions and are able to provide relevant examples and non-examples. Students with moderate conceptual understanding can restate concepts and classify plant parts but still experience misconceptions that require further reinforcement. Meanwhile, students with low conceptual comprehension have difficulty in restating concepts or classifying plant parts, requiring a more intensive learning approach. Factors that affect students' understanding of science concepts include internal factors such as learning interest and concentration in learning as well as external factors such as lack of learning media and student learning environment